How to win at feminism : the definitive guide to having it all--and then some! - Newell, Elizabeth; Pappalardo, Sarah (New York Harper Collins, 2016)
"Feminism is all about demanding equality and learning to love yourself. But not too much - men hate that! From the writers of Reductress, the subversive, satirical women's magazine read by over 2.5 million visitors a month, comes HOW TO WIN AT FEMINISM: The Definitive Guide to Having It All--And Then Some! This ultimate guide to winning feminism--filled with four-color illustrations, bold graphics, and hilarious photos--teaches readers how to battle the patriarchy better than everybody else. From the herstory of feminism to how to apologize for having it all, readers will learn how to be a feminist at work and at home with tips that include: How to Do More with 33 Cents Less How to Be Sex-Positive Even When You're Bloated How to Love Your Body Even Though Hers Is Better The 9 Circles of Hell for Women Who Don't Help Other Women Designer Handbags to Hold All Your Feminism How to Get Catcalled For Your Personality HOW TO WIN AT FEMINISM is a fresh take on women's rights through the lens of the funniest women in comedy today. With this book as your wo-manual, you'll shatter that glass ceiling once and for all (but you'll still need to clean up the mess)"--
Keywords: Feminist theory; Feminism; Sex role; Women's rights; HUMOR / Topic / Adult; SOCIAL SCIENCE / Feminism & Feminist Theory; SOCIAL SCIENCE / Women's Studies